Penerapan Terapi Bermain Mewarnai Tas Kain untuk Menurunkan Kecemasan Anak Preoperasi - Nengah Galih Paitwijaya; Ketut Suryani; Novita Anggraini (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Anxiety in children undergoing surgery is a common issue stemming from fear of the procedure, the hospital environment, and the invasive nature of the treatment. Unaddressed anxiety can affect a child's psychological well-being and hinder the care process. Play therapy—specifically coloring—is a nursing intervention that can help alleviate this anxiety. Coloring serves as an activity that provides distraction, promotes a sense of comfort, and helps children express their emotions during their care. The objective of this implementation was to assess changes in anxiety levels among preoperative children following a cloth-bag coloring play therapy intervention. This final nursing project employed a case study method incorporating Evidence-Based Practice, specifically cloth-bag coloring play therapy, with three preschool-aged respondents scheduled for surgery. Anxiety levels were measured before and after the intervention using the Face Image Scale (FIS). The results demonstrated a reduction in anxiety levels across all respondents: the first respondent's score dropped from 4 to 2, the second from 3 to 2, and the third from 4 to 2. Cloth-bag coloring play therapy can be utilized to reduce anxiety levels in preschool children undergoing surgery